Protective effects of a wheat cultivar mixture against splash‐dispersed septoria tritici blotch epidemics. (20th November 2012) - Gigot, C.; Saint‐Jean, S.; Huber, L.; Maumené, C.; Leconte, M.; Kerhornou, B.; de Vallavieille‐Pope, C.
Abstract : The use of cultivar mixtures to control foliar fungal diseases is well documented for windborne diseases, but remains controversial for splash‐dispersed diseases. To try to improve this strategy, a cultivar mixture was designed consisting of two wheat cultivars with contrasted resistance to Mycosphaerella graminicola, responsible for the rainborne disease septoria tritici blotch (STB), in a 1:3 susceptible:resistant ratio rather than the 1:1 ratio commonly used in previous studies. The impact of natural STB epidemics in this cultivar mixture was studied in field experiments over 4 years. Weekly assessments of the number of sporulating lesions, pycnidial leaf area and green leaf area were carried out on the susceptible cultivar. In years with sufficient STB pressure, disease impacts on the susceptible cultivar in the mixture were always significantly lower than in the pure stand (e.g. 42% reduction of pycnidial leaf area for the three upper leaves in 2008 and 41% in 2009). In years with low STB pressure (2010 and 2011), a reduction of disease impacts was also shown but was not always significant. After major rainfall events, the number of sporulating lesions observed on the susceptible cultivar after one latent period was reduced on average by 45% in the mixture compared to the pure stand. All the measurements showed that a susceptible cultivar was consistently protected, at least moderately, in a mixture under low to moderate STB pressure. Therefore, the results prove that the design of an efficient cultivar mixture can include the control of STB, among other foliar diseases.